Implementasi Strategi Promosi dan Kualitas Pelayanan terhadap Nilai Pelanggan serta Implikasinya Tingkat Hunian Kamar - Aini Kusniawati (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2017)
The Purpose of this investigation are to obtain the empirical evidence and to find out the clarity of phenomenon, and the conclusion about the implementation of strategic promotion and the service quality towards the customer value and its implication on the room occupancy rate in the non-star hotels in the area of East Priangan. This investigation result is expected to provide the contribution to the development of management in general and especially in the development of marketing management. The approach used in this investigation is quantitative approach with descriptive and inductive methods, namely to collect, present, analyze, examining the hypotheses, and arranging the conclusions and suggestions. Whereas the conclusions are obtained based on the investigation and data analyze are as follows: 1. The implementation of strategic promotion (pull), strategic promotion (push), and quality service of non-star hotels in the area of East Priangan according to the customer perception in 2010 is good enough. 2. The customer value of non-star hotels in the area of East Priangan according to the customer perception in 2010 is good enough. 3. The occupation level if non-start hotels in the area of East Priangan according to the customer perception in 2010 are good enough. 4. There is simultaneous influence a partial implementation of strategic promotion (pull), strategic promotion (push), and the quality service towards the customer value of non-star hotels in the area of East Priangan. The greatest contribution derives from the implementation of quality service whereas the least contribution derives from the strategic promotion (push). 5. There is an influence of customer value towards the occupancy rate of non-star hotels’ room in the area of East Priangan. The results of this investigation confirm that the implementation of strategic promotion and quality service in forming the customer value is very essential as it can increase the ratio of room occupancy by the customers.